Dispensing Oral Temozolomide in Children: Precision and Stability of a Novel and Ready to Use Liquid Formulation in Comparison with Capsule Derived Mixtures - Caroline Lemarchand; Hugues Bienaymé; André Rieutord; Samuel Abbou; Maxime Annereau; Jeremy Bastid (MDPI AG, 2023)
Temozolomide (TMZ) is part of the therapeutic armamentarium used in managing pediatric cancers; however, available oral forms (capsules) are not adapted for use in children. Our aim was to assess the dose accuracy and stability of TMZ using capsule contents mixed with food compared with a novel, ready-to-use liquid formulation specifically developed for children (Ped-TMZ, brand name KIZFIZO). Dose accuracy and TMZ stability testing were performed with TMZ capsule contents (90 mg) mixed with food vehicles (apple juice, apple sauce, cream, milk, and mashed potatoes) and compared to an equivalent dose of Ped-TMZ. Acceptance criteria were predefined for TMZ (95.0-105.0%) and its degradation product amino-imidazole-carboxamide (AIC; <1%) content. The delivered dose was significantly higher using Ped-TMZ (96.6 ± 1.2%) and within the predefined criteria for TMZ content, whereas it was systematically under the lower specifications of 95% using capsule-derived preparations with apple juice (91.0 ± 1.5%) and apple sauce (91.6 ± 1.4%), respectively (p < 0.0001). In chemical stability tests, the four food vehicles (apple sauce, cream, milk, mashed potatoes) had a significant effect on TMZ stability (p = 0.0042), and the AIC significantly increased with time in three of the four vehicles (p < 0.0001). Only 1/72 of preparations from capsules met the predefined acceptance criteria, whereas Ped-TMZ showed no TMZ loss, and the AIC remained within specifications. In conclusion, mixing TMZ capsule content with food may result in significant underexposure, possibly even greater in routine practice, as complete food intake by the child is unlikely.